Rethinking how gender matters for food security. - Kawarazuka, Nozomi; Locke, C.; Seeley, J. (2017)
In agricultural research, gender has been recognised as a critical issue that needs to be addressed to enhance household food security. However, prioritising gender is often taken to signify a focus on women, with most attention given to women’s lack of access to land and resources. Consequently, the complex processes of how gender influences household food security are relatively poorly understood. In contrast, ethnographic evidence shows that both women’s and men’s strategies for household food security are highly gendered and that women’s, as well as men’s, approaches to coping with insecure lives are far more diverse than simply ensuring direct access to economic resources. With reference to this established evidence, we highlight how women and men negotiate for food security, and consider the implications for agricultural research.